2014
DOI: 10.1002/nav.21594
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of noncollaborative servers in two‐stage tandem queueing systems

Abstract: We consider two‐stage tandem queueing systems with dedicated servers in each station and a flexible server that is trained to serve both stations. We assume no arrivals, exponential service times, and linear holding costs for jobs present in the system. We study the optimal dynamic assignment of servers to jobs assuming a noncollaborative work discipline with idling and preemptions allowed. For larger holding costs in the first station, we show that (i) nonidling policies are optimal and (ii) if the flexible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Lemma 1 states that the minimum expected cost increases with the number of jobs in the system. It can be proved by induction on the number of jobs (as in [15]) or by straightforward sample path arguments.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemma 1 states that the minimum expected cost increases with the number of jobs in the system. It can be proved by induction on the number of jobs (as in [15]) or by straightforward sample path arguments.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
“…The necessity of the condition is proved in the next section (Theorem 4). The sufficiency is a consequence of the following lemma, whose proof can be obtained by induction on the number of jobs in Station 2 (see [15]) or by sample path arguments.…”
Section: A Optimality Of Non-idling Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a non-idling discipline for at least the dedicated servers was assumed. Both of these conditions were relaxed by Pandelis [59]. For clearing systems he showed that non-idling policies are optimal when the holding cost rate in the upstream station is not less than the corresponding rate in the downstream station, and for this case he provided conditions on service rates that ensure that the optimal server allocation is characterized by a single switching curve under a non-collaborative service discipline.…”
Section: Related Literaturementioning
confidence: 99%